Control of a motorboat with the Transverse Function approach. Issue 19 (2015) - Hamel, T.; Samson, C.
Abstract: The Transverse Function (TF) control approach is applied to the control of a generic motorboat endowed with a surge force along the stern-bow direction and a torque actuation to modify the boat's orientation. With respect to more conventional methods this approach allows for uniform practical stabilization of any reference position/orientation trajectory. This includes fixed-points in the absence of sea-currents, whose asymptotic stabilization cannot be achieved by classical feedback controllers, and non-feasible trajectories, i.e. trajectories that are not solutions to the system's motion equations and thus cannot be stabilized asymptotically.